Basic Graphic Design Training for High School Students (SMK Sjakhyakirti) - Azhar Andika Putra; Nia Umilizah; Pipin Octavia; Rudiansyah; Fakhri Lambardo (JARDIRA – Jurnal Pengabdian Digital dan Rekayasa Informatika, 2025)
Background : Graphic design is a visual skill that plays a crucial role in modern digital communication, particularly in marketing, social media, advertising, and branding. The growing industry demand for creative workers requires vocational education institutions, such as vocational high schools (SMK), to equip students with skills relevant to the times. However, many students still lack adequate conceptual and technical understanding in this field . Contribution:To address these challenges, SMK Sjakhyakirti provides comprehensive basic graphic design training. This program aims not only to enhance students' theoretical understanding of visual design principles but also to develop technical skills in using professional design software. This training also serves as a model for implementing vocational training that is relevant and adaptive to developments in the creative industry . Method: The training uses a blended learning approach that combines online and face-to-face learning, supported by project-based learning methods , tool demonstrations, hands-on practice, and formative and summative evaluations. Students are actively involved in visual media creation projects such as posters, logos, and brochures using Adobe Photoshop, Illustrator, and CorelDRAW . Results : The evaluation showed significant improvements in five key aspects: understanding design concepts (87%), software proficiency (91%), creativity (78%), team collaboration (83%), and understanding design ethics (85%). The overall average score reached 4.24 on a scale of 5, indicating the training's effectiveness in improving student competency. This program is expected to provide a strong foundation for students to pursue careers in the increasingly competitive creative industry. Conclusion: The basic graphic design training program at SMK Sjakhyakirti has proven to be an effective initiative in enhancing students' competencies in both conceptual understanding and technical execution of visual communication. Through a well-structured blended learning model and hands-on project-based activities, students demonstrated notable progress across various competencies, including software proficiency, creativity, collaboration, and ethical design awareness. With an average achievement score of 4.24 out of 5, this program not only meets the demands of the current creative industry but also serves as a replicable model for other vocational institutions aiming to equip students with future-ready skills in digital design